If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8x + -9 = -9x + -1 Reorder the terms: -9 + -8x = -9x + -1 Reorder the terms: -9 + -8x = -1 + -9x Solving -9 + -8x = -1 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. -9 + -8x + 9x = -1 + -9x + 9x Combine like terms: -8x + 9x = 1x -9 + 1x = -1 + -9x + 9x Combine like terms: -9x + 9x = 0 -9 + 1x = -1 + 0 -9 + 1x = -1 Add '9' to each side of the equation. -9 + 9 + 1x = -1 + 9 Combine like terms: -9 + 9 = 0 0 + 1x = -1 + 9 1x = -1 + 9 Combine like terms: -1 + 9 = 8 1x = 8 Divide each side by '1'. x = 8 Simplifying x = 8
| 8n+5=3n+30 | | 8(10x)=640 | | 2r+8=12r | | 5x-4x-10=4-7 | | 4t^2-8t+3=0 | | -11=x+(-16) | | 3x+10+15=2x+50 | | 4(3n-1)=24 | | z-13=-10 | | -14=-6m+7 | | y-10=15 | | 12u-91=5u | | (9-x)-6=1 | | -9-t=5 | | 7x=x+38 | | 12-x=x+6 | | x+3x=-24 | | -7+4x=-27 | | 6ab-8a+21b-28= | | 6a^2+3ab+10a+5b= | | 14-x=7-x | | 2m+30=7m-5 | | x^3-5x^2-7=0 | | 3k-0.75=k-0.5 | | 12a^3b+8a^2b^2-20ab^3= | | -7x-3=53 | | 3x+11-x=x+7 | | 4x+20=-30 | | 4xy^2-16x= | | (x+6)-(x-7)=(4x+20)-(3+5x) | | 2.10+0.80x=11.70 | | 7x+18=125 |